Bioassays and Biosensors for Rapid Detection and Analysis - Zhang, Zhen (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The fast development of biosensors with high sensitivity through new functional materials introduced, or simplified the procedure in measurements, which is definitely important. However, more attentions should be paid for real applications, increasing tolerances against various matrix that potentially influence the performance of biosensors. This reprint focuses on the biosensors which were widely used in various fields after some problems were circumstanced, analytical methods development for containments in environments and foods, and biomarkers/hazardous substances in cells based on nanozyme or other nanoparticles, combined with antibodies, nucleic acids, aptamers or nanobodies, including enough sensitivity and satisfactory accuracy, maintaining enzyme activity at varied harsh environments.